Design and synthesis of some new benzoylthioureido phenyl derivatives targeting carbonic anhydrase enzymes - Mazin A. A. Najm; Walaa R. Mahmoud; Azza T. Taher; Safinaz E-S. Abbas; Fadi M. Awadallah; Heba Abdelrasheed Allam; Daniela Vullo; Claudiu T. Supuran (Taylor & Francis Group, 2022)
The present study aimed to develop potent carbonic anhydrase inhibitors (CAIs). The design of the target compounds was based on modifying the structure of the ureido-based carbonic anhydrase inhibitor SLC-0111. Six series of a substituted benzoylthioureido core were prepared featuring different zinc-binding groups; the conventional sulphamoyl group 4a-d and 12a-c, its bioisosteric carboxylic acid group 5a-d and 13a-c or the ethyl carboxylate group 6a-d and 14a-c as potential prodrugs. All compounds were assessed for their carbonic anhydrase (CA) inhibitory activity against a panel of four physiologically relevant human CA isoforms hCA I and hCA II, and hCA IX, and hCA XII. Compounds 4a, 4b, 4c, 4d, 5d, 12a, and 12c revealed significant inhibitory activity against hCA I that would highlight these compounds as promising drug candidates for the treatment of glaucoma.